Flexural behaviour of an innovative connection for structural sandwich panels - Lameiras, Rodrigo Melo (2018)
This paper presents the results experimental work conducted with composite beam specimens that are part of a series of studies to determine the feasibility of using a new type of shear connector, called PERFOFRP, in Steel Fibre Reinforced Self-Compacting Concrete (SFRSCC) structural sandwich wall panels. The connector is consisted of a flat Glass Fiber Reinforced Polymer (GFRP) plate with aligned holes evenly distributed along its length. The perforated part of connector is embedded in the concrete layers and the connection is materialized by the combined effects of friction/adhesion and of the mechanical interlock between the perforated laminate and the concrete dowels formed by the concrete that pass through the holes. Previously, the authors of the present paper investigated the mechanical behaviour of connections made with PERFOFRP connectors under transversal loads. Nonetheless, up to now, no investigation was published on the flexural behaviour of sandwich panels produced with the PERFOFRP connectors. In the present paper, the overall mechanical behaviour of the connection under flexure was investigated, being reported: failure modes, stiffness and ultimate flexural capacities of composite beams. The impact of using connectors made with two different types of GFRP laminates were investigated on the mechanical behaviour of composite beams was investigated.